2013
DOI: 10.3906/tar-1210-28
|View full text |Cite
|
Sign up to set email alerts
|

Is Quercus virgiliana a distinct morphological and genetic entity among European white oaks?

Abstract: 2-Morpholine-4ylethyl-3 H -1,2,4-triazole-3-ones (2a, 2b) were obtained from the condensation between the corresponding ethoxycarbonylhydrazones and 2-morpholinoethanamine. 2a was converted to acetohydrazide (4) via the formation of an ester derivative (3). Treatment of 2a and 2b with several aryl sulfonyl chlorides afforded the corresponding 2-arylsulfonyl-1,2,4-triazole-3-ones (5a-c and 6). The reaction of hydrazide (4) with benzyl iso-and benzyl isothiocyanate produced the corresponding carboxamide (8a) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Obviously we do not consider this work to be a solution to all the problems concerning the taxonomy of white pubescent oaks, not even to some of them of topical relevance in south-eastern Europe, such as the eternal debate on the dualism between Q. pubescens and Q. virgiliana (cf. Borazan and Babaç 2003, Škvorc et al 2005, Franjić et al 2006, Jerše and Batič 2007, Trinajstić 2007, Enescu et al 2013. We simply believe that this work represents a small step forward, a substantial contribution, albeit on a regional scale, to being able to arrive in the near future at a possible solution of the problem on a global scale.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Obviously we do not consider this work to be a solution to all the problems concerning the taxonomy of white pubescent oaks, not even to some of them of topical relevance in south-eastern Europe, such as the eternal debate on the dualism between Q. pubescens and Q. virgiliana (cf. Borazan and Babaç 2003, Škvorc et al 2005, Franjić et al 2006, Jerše and Batič 2007, Trinajstić 2007, Enescu et al 2013. We simply believe that this work represents a small step forward, a substantial contribution, albeit on a regional scale, to being able to arrive in the near future at a possible solution of the problem on a global scale.…”
Section: Discussionmentioning
confidence: 87%
“…The level of genetic variability within the pubescent oak populations of the Apulia region was here found to be lower than that reported for Q. pubescens in other countries. Curtu et al (2007b) reported aH e = 0.891, Ar = 17.8 on a study based on 6 microsatellite loci for 73 Q. pubescens individuals while Enescu et al (2013) reported aH e =0.847, k = 22 and Ar = 14.22 in a 7 microsatellite loci study in a geographically related area. The heterozygosity values reported in these studies, however, would not be directly comparable with those obtained by us due to the use of different type of markers (genomic SSRs vs. EST-SSRs).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the taxonomical framework of Southern Europe the Q. pubescens species complex remains an unresolved tangle. Papers published in Southern Europe in the last fifteen years regarding the morphological variability of the European white oaks have been moving in more or less the same direction: that a critical evaluation of the many oak taxa is needed regardless of whether they were included in the national floras or checklists as accepted species or not (Franjic et al 2006;Enescu et al 2013;Wellstein and Spada 2015;Di Pietro et al 2016, 2020.…”
Section: Discussionmentioning
confidence: 99%
“…However, as underlined in Denk et al (2017), the major challenge for future studies is to establish the molecular and morphological circumscription at species rank and their biogeographic and ecological characterization. In the last two decades important results have been achieved in identifying the occurrence (or the absence) of species boundaries between taxonomically critical groups of sympatric Southern-European white oaks using molecular markers (Bruschi et al 2000;Jedináková-Schmidtová et al 2004;Franjic et al 2006;Fortini et al 2009;Curtu et al 2011;Enescu et al 2013;Crăciunescu et al 2015;Di Pietro et al 2020). In our opinion, the necessary further step should be to link discontinuities highlighted at the genomic level to a well-defined and unambiguous set of diagnostic morphological, ecological and coenological characters to circumscribe oak species.…”
Section: The Concept Of Species In Quercusmentioning
confidence: 99%